Vehicular Cloud for Smart Driving Using Internet of Things. - Vijayarangam, S.; Megalai, J.; Krishnan, Sivakumar; Nagarajan, Sivakumar; Devi, M. Ramya; Lokesh, S. (Journal of Medical Systems, 2018)
The vehicular cloud can be made more reliable by having minimum number of vehicles and their accessibility of the vehicles in the given lane; in addition reliability can also be made using the function called movement of vehicles. The number of vehicles present in the area determines the task that can be accessed in the area and with the help of travelling time of the vehicles the validity of the lane can be determined. In this paper, a research is carried based on the stochastic investigation on the some of attributes of traffic with the help of cloud in street portion to accept the necessary attribute prototypes. In this paper two types of activity is done, first one is free flow movement of vehicle and second one is queuing- up activity. For the first activity, a noticeable traffic model is used to find the free flow movement of the vehicle and some parameters like activity thickness, living time and quantity of vehicles. In case of second activity queuing up model is used to find queue flow and parameters like length of line and time in the line are found. The research outcome will be given to all peoples in road traffic and traffic is the problem in many developed countries and they can be free from traffic. This model suggests an alternate route for the user which is free from traffic.